A signature of saliva-derived exosomal small RNAs as predicting biomarker for esophageal carcinoma: a multicenter prospective study - Li, Kai; Lin, Yusheng; Luo, Yichen; Xiong, Xiao; Wang, Lu; Durante, Kameron; Li, Junkuo; Zhou, Fuyou; Guo, Yi; Chen, Shaobin; Chen, Yuping; Zhang, Dianzheng; et al. (Molecular cancer, 2022)
The tRNA-derived small RNAs (tsRNAs) are produced in a nuclease-dependent manner in responses to variety of stresses that are common in cancers. We focus on a cancer-enriched tsRNA signature to develop a salivary exosome-based non-invasive biomarker for human esophageal squamous cell carcinoma (ESCC). Cancer-enriched small RNAs were identified by RNA sequencing of salivary exosomes obtained from ESCC patients (n = 3) and healthy controls (n = 3) in a pilot study and further validated in discovery cohort (n = 66). A multicenter prospective observational study was conducted in two ESCC high-incidence regions (n = 320 and 200, respectively) using the newly developed biomarker signature. The tsRNA (tRNA-GlyGCC-5) and a previously undocumented small RNA were specifically enriched in salivary exosomes of ESCC patients, ESCC tissues and ESCC cells. The bi-signature composed of these small RNAs was able to discriminate ESCC patients from the controls with high sensitivity (90.50%) and specificity (94.20%). Based on the bi-signature Risk Score for Prognosis (RSP), patients with high-RSP have both shorter overall survival (OS) (HR 4.95, 95%CI 2.90-8.46) and progression-free survival (PFS) (HR 3.69, 95%CI 2.24-6.10) than those with low-RSP. In addition, adjuvant therapy improved OS (HR 0.47, 95%CI 0.29-0.77) and PFS (HR 0.36, 95%CI 0.21-0.62) only for patients with high but not low RSP. These findings are consistent in both training and validation cohort. The tsRNA-based signature not only has the potential for diagnosis and prognosis but also may serve as a pre-operative biomarker to select patients who would benefit from adjuvant therapy. A prospective study of diagnosis biomarkers of esophageal squamous cell carcinoma, ChiCTR2000031507 . Registered 3 April 2016 - Retrospectively registered.